Myanmar: Surga Yang Hilang - Dewi Maria Herawati; Agung Yudhistira Nugroho (PRoMEDIA, 2021)
AbstractMyanmar has a diversity of tribes and cultures, as well as unspoiled natural scenery to be one of the best potentials in its tourism sector. This can be a positive image for the country. However, Myanmar is also a country that has a long and winding history. Starting from a rich kingdom, colonized, independent, coup and the existence of divisions, to reforms which then experienced a coup again. Judging from the long history of this country, this article describes the nation branding inherent in Myanmar due to the intrigue that occurs in it. To see this phenomenon, the theoretical approach of Anholt's Nation Branding theory is used as a literature review. From this theory, it is concluded that the politically unstable state of the country certainly has a negative impact on the image of the country itself. The country's political instability has hampered economic growth, infrastructure and human resource development, causing the tourism sector to suffer. All of these things affect the nation branding for Myanmar. Therefore, the journey to change Myanmar's image as a competitive tourism destination in the eyes of the world will be a long journey.Keywords: Myanmar, Anholt, Nation BrandingAbstraksiMyanmar memiliki keberagaman suku dan budaya, serta panorama alam yang masih alami untuk dapat menjadi salah satu potensi terbaik di sektor pariwisatanya. Hal ini dapat menjadi citra yang positif bagi negara tersebut. Namun, Myanmar juga merupakan negara yang memiliki sejarah panjang yang cukup berliku. Mulai dari kerajaan yang kaya, dijajah, merdeka, dikudeta dan adanya perpecahan, hingga reformasi yang kemudian mengalami kudeta kembali.  Melihat dari panjangnya sejarah negara ini, maka artikel ini menggambarkan nation branding yang melekat di Myanmar diakibatkan intrik yang terjadi didalamnya. Untuk melihat fenomena tersebut, pendekatan teoritis dari teori Nation Branding dari Anholt digunakan sebagai telaah literatur. Dari teori tersebut, disimpulkan bahwa kondisi negara yang tidak stabil secara politik tentu berdampak negatif bagi citra negara itu sendiri. Ketidakstabilan politik negara mengakibatkan pertumbuhan ekonomi, infrastruktur dan pengembangan sumber daya manusia menjadi terhambat sehingga menyebabkan sektor pariwisata pun mendapatkan imbasnya. Semua hal tersebut saling mempengaruhi nation branding bagi Myanmar. Oleh karena itu, perjalanan untuk mengubah citra Myanmar sebagai tujuan pariwisata yang kompetitif di mata dunia akan menjadi perjalanan yang panjang.Kata Kunci: Myanmar, Anholt, Nation Branding